Stability and in vitro release behaviour of encapsulated omega fatty acid-rich oils in lentil protein isolate-based microcapsules. (2nd January 2018) - Chang, C.; Nickerson, M. T.
Abstract: The objective of this study was to investigate the use of a lentil protein isolate-based microcapsule design as a platform for entrapping different types of omega fatty acid-rich oil (e.g. canola, fish and flaxseed oils) and to characterise differences in the physical properties (e.g. moisture content, water activity, colour, wettability, particle size, surface oil and entrapment efficiency), storage stability and in vitro release behaviour of the entrapped oils. All microcapsules displayed similar physical properties regardless of the core material. Free fatty acid content, peroxide value, 2-thiobarbituric acid reactive substances and accelerated oxidation test were investigated between the free and encapsulated oils to determine protective effects from microencapsulation and found the wall material provided the greatest protective effect to the fish oils relative to the others. Based on an in vitro release assay, it was proposed that different intrinsic properties of fatty acids (e.g. polarity, conformation, chain length and number of double bonds) led to different release properties under simulated conditions. For instance, more encapsulated canola oil (∼8.9%) was released within simulated gastric fluid, whereas more encapsulated fish oil (∼73.4%) was released within simulated gastrointestinal fluids. Overall, the capsule design used in this study could be potentially used as a universal platform to deliver more healthy oils.